2020
DOI: 10.7759/cureus.7454
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intimal Neovessels Noted by Optical Coherence Tomography with Cardiac Allograft Vasculopathy

Abstract: Background Cardiac allograft vasculopathy (CAV) is a leading cause of graft failure in cardiac transplant recipients. Progression of intimal thickening noted during routine surveillance intracoronary imaging is associated with the development of CAV. However, mechanisms of CAV development are poorly understood and targets for therapy modification remain elusive. We investigated the association of neovessels (INs) within the intima, noted by optical coherence tomography (OCT) during routine CAV surveillance ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Another study evaluating VV by OCT and the change in plaque volume by serial IVUS tests showed a significant association between the VV volume and the progression of plaque volume [53]. Another recent study also showed the significant association of OCT-detected neovessels within the intima with CAV [54]. These findings suggest that neovascularization may be a potential predictor and possible therapeutic target to attenuate CAV.…”
Section: Coronary Angiography Intravascular Ultrasound and Optical Co...mentioning
confidence: 92%
“…Another study evaluating VV by OCT and the change in plaque volume by serial IVUS tests showed a significant association between the VV volume and the progression of plaque volume [53]. Another recent study also showed the significant association of OCT-detected neovessels within the intima with CAV [54]. These findings suggest that neovascularization may be a potential predictor and possible therapeutic target to attenuate CAV.…”
Section: Coronary Angiography Intravascular Ultrasound and Optical Co...mentioning
confidence: 92%
“…40 Multiple studies have reported an association between microchannels and layered complex plaque, supporting the role of neovascularization in CAV. [40][41][42] In a study of 45 transplant recipients, intimal neovessels were detected by OCT in 49% of the patients and were associated with a greater risk of angiographic CAV and greater MIT. 42 Another study found that the presence of lipid pools, thin-cap fibroatheromas, macrophages, and microchannels on OCT at baseline was associated with increased plaque volume by IVUS at 1-year follow-up.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…[40][41][42] In a study of 45 transplant recipients, intimal neovessels were detected by OCT in 49% of the patients and were associated with a greater risk of angiographic CAV and greater MIT. 42 Another study found that the presence of lipid pools, thin-cap fibroatheromas, macrophages, and microchannels on OCT at baseline was associated with increased plaque volume by IVUS at 1-year follow-up. 43 Finally, several studies have demonstrated an association between a history of high-grade acute cellular rejection as well as the presence of donor-specific antibodies and abnormal OCT findings such as macrophage infiltration and intimal thickening with negative remodeling.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…27 Chahal and colleagues evaluated 45 transplant patients with angiography and OCT, and found that intimal neovessels were seen by OCT in 49% of patients, and intimal neovessels were associated with angiographic CAV, increasing intimal thickness, increasing transplant age, and hypertension. 28…”
Section: Neovascularization In Cavmentioning
confidence: 99%
“…27 Chahal and colleagues evaluated 45 transplant patients with angiography and OCT, and found that intimal neovessels were seen by OCT in 49% of patients, and intimal neovessels were associated with angiographic CAV, increasing intimal thickness, increasing transplant age, and hypertension. 28 Neovascularization is therefore a feature of CAV not detected by standard imaging techniques, and OCT is providing new insights as to its prevalence, distribution, and association with clinical events. While currently poorly understood, neovascularization as a therapeutic target in CAV may hold promise.…”
Section: Neovascularization In Cavmentioning
confidence: 99%